Negligible Effect of Quercetin in the Pharmacokinetics of Sulfasalazine in Rats and Beagles: Metabolic Inactivation of the Interaction Potential of Quercetin with BCRP - Ju-Hee Oh; Dokeun Kim; Haejun Lee; Gyeonghee Kim; Taehoon Park; Min Chang Kim; Young-Joo Lee (MDPI AG, 2021)
Breast cancer resistance protein (BCRP) mediates pharmacokinetic drug interactions. This study evaluated the potential of quercetin to inhibit and induce BCRP in vitro and in vivo. The inhibition of BCRP was investigated for quercetin and its metabolites using BCRP/mBcrp1-overexpressing MDCKII cells by flow cytometry. The induction of BCRP was investigated in LS174T cells using quantitative PCR. The expression of rat BCRP in rat small intestine, liver, and kidney was also measured after multiple administrations of quercetin in rats (50, 100, and 250 mg/kg, seven days). The in vivo pharmacokinetic changes of sulfasalazine following single or multiple administration of quercetin in rats and beagles were investigated. Although the induction effect of quercetin on BCRP was observed in vitro, the in vivo expression of rat BCRP was not changed by multiple quercetin administrations. Oral administration of quercetin did not affect the plasma concentration or pharmacokinetic parameters of sulfasalazine, regardless of dose and dosing period in either rats or beagles. In addition, the inhibitory effect of quercetin metabolites on BCRP/mBcrp1 was not observed. These results suggest that the in vivo drug interaction caused by quercetin via BCRP was negligible, and it may be related to the metabolic inactivation of quercetin for the inhibition of BCRP.